PEMANFAATAN LIMBAH DAGING BUAH PALA TUA DI MALUKU - Dumadi, Suryatmi Retno (BPPT)
It was until the end of 2007, the meat of nutmeg was abandoned near the trees, in Mollucas Islands, especially in Ambon island and Banda island. The nutmeg meat was considered as waste of nutmeg agribusiness. An effort to make the waste become a valuable product had been done. It was used as the raw material of nutmeg syroop which gives added value to nutmeg and benefi t to those who drink it. The process and apparatus to make the syroop were simple, it begin with extraction of nutmeg meat, sterilization of the syroop container, mixing the extract with sugar, bottling, labeling. With the ratio of extracted juice to sugar 1:1, the product have good taste and fl avor, which was preferred by panels. The syroop produced contained vitamine C 1,22% and reduced sugar of 25,35%. Financial analysis showed the profi t of this product was Rp.10.000,- per bottle and could be increased by expanding market and production.Keywords : Waste of nutmeg, abandoned, added value, extracted juice, syroop, profi t, market, taste, flavor